Capillary hemangioma of the testis: A rare benign tumour - Wong, Nathan Colin; Dason, Shawn; Pozdnyakov, Sergey; Alexopoulou, Iakovina; Greenspan, Michael (Canadian Urological Association Journal, 2015)
Testicular capillary hemangioma is a rare benign vascular tumour. We report a case of a 66-year-old man who underwent an uncomplicated radical orchiectomy for a painless left testicular mass. Pathology showed capillary hemangioma of the testis. There are only 22 cases reported in the English literature, including the presented case. Appropriate intra-operative recognition of this entity is vital to assess for potential testicular-sparing surgery.